Training on Writing Scientific Articles in Improving Competence for Teachers in Gunungsari Serang Banten: Pelatihan Penulisan Artikel Ilmiah dalam Meningkatkan Kompetensi bagi Guru-Guru di Gunungsari Serang Banten - Surti Zahra; Nugrahini Kusumawati; Mamay Komarudin; Jaka Wijaya Kusuma; Hamidah Hamidah (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Writing an article from the results of the study may be something difficult for those who are not familiar with it. As a teacher or educator, it is appropriate to have the ability to write scientific articles so that students have a model for school academic life. The low productivity of teachers in writing scientific publications is a problem related to professionalism. Likewise, teachers who teach in schools in Ciherang village, Gunung Sari district, still do not participate in research activities, rarely conduct research in their fields, and lack understanding of articles and scientific publications. Based on these problems, the community service team of Bina Bangsa University carried out training on writing scientific articles. The implementation method has two stages, namely the preparation stage and the training implementation stage. 19 teacher participants attended the training. After the training, the teacher's insight and knowledge about writing scientific articles increases and the teacher can improve his professionalism